Does Privacy Regulation Harm Content Providers? A Longitudinal Analysis of the Impact of the GDPR - Lefrere, Vincent; Warberg, Logan; Cheyre, Cristobal; Marotta, Veronica; Acquisti, Alessandro (Management Science, 2026)
Concerns that the European General Data Protection Regulation (GDPR) would adversely affect the ability of news and media websites to create new quality content have not been thoroughly investigated in the literature. We construct a longitudinal data set of European Union (EU) and U.S. news and media websites to study how online content providers responded to the GDPR over time and whether potential restrictions on online tracking enforced by the regulation affected their downstream outcomes. We find robust evidence that both EU and U.S. news and media websites responded to the regulation by altering their data collection practices, but did so differently, with EU websites reducing tracking and implementing consent mechanisms at higher rates than their U.S. counterparts. Although we detect a reduction in average page views per user on EU relative to U.S. websites, we do not find evidence of negative impacts, in both the short and long term, on EU websites’ provision of new content or on several proxies for quality of that content, such as social media engagement metrics, various traffic measures, and articles’ text analytics. We also find no evidence of differences in survival rates across EU and U.S. news and media websites, and no evidence that monetization strategies changed at higher rates on EU relative to U.S. websites. The analysis suggests that EU online content providers did implement changes to their data collection practices in response to the GDPR but were able to use data minimization and consent mechanism strategies that allowed them to keep producing content and engage audiences at degrees on par with their U.S. counterparts. This paper was accepted by D. J. Wu, information systems. Funding: The authors gratefully acknowledge support from the Alfred P. Sloan Foundation, CARNOT Télécom & Société numérique, DATAIA Convergence Institute (as part of the Programme d’Investissement d’Avenir [Grant ANR-17-CONV-0003] operated by Institut Mines Telecom, Business School Project YPOOG), the French National Research Agency [Grant ANR-21-CE23-0031-02], and the National Science Foundation [Awards 2237327, 2237328, and 2237329]. Supplemental Material: The online appendices and data files are available at https://doi.org/10.1287/mnsc.2022.03186 .